2017
DOI: 10.1136/jim-2016-000295
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Acarbose in Treating Elderly Patients with Diabetes with Postprandial Hypotension

Abstract: Chinese Clinical Trial Registry ChiCTR-IPR-15006177.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…All the included trials were evaluated as having a certain bias risk ( Figure 2 ). Three of the trials reported using the specific random method ( 13 , 16 , 17 ). All studies did not mention the allocation concealment method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the included trials were evaluated as having a certain bias risk ( Figure 2 ). Three of the trials reported using the specific random method ( 13 , 16 , 17 ). All studies did not mention the allocation concealment method.…”
Section: Resultsmentioning
confidence: 99%
“…All studies did not mention the allocation concealment method. One study reported the single-blind method for patients ( 16 ). All the studies did not have sufficient reports to determine the bias of selective reporting results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding other drugs, pyridostigmine and atomoxetine can increase sympathetic activity and have shown some encouraging results in single‐dose studies . Acarbose has been reported to ameliorate postprandial OH and may be considered in such cases . Other agents that have been tested in specific conditions that coexist with OH are erythropoietin in anemia, desmopressin in nocturnal polyuria, and octreotide in postprandial OH, but evidence supportive of clinical benefit is weak .…”
Section: Treatmentmentioning
confidence: 99%
“…The effect of α-GIs to decrease blood glucose and insulin levels and prevent the development of type 2 diabetes in patients with impaired glucose tolerance is well established [ 8 , 9 , 10 , 11 , 12 , 21 ]. There is limited evidence demonstrating an effect of α-GIs to enhance satiety [ 8 , 10 ], and none of them have reported its effect on both satiety and gastrointestinal hormones.…”
Section: Discussionmentioning
confidence: 99%